Low Birth Weight Babies Born to Mothers Admitted to Gynecology and Obstetrics Department of Dhaka Medical College Hospital (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: World health organization estimates that 25 million low birth weight (LBW) babies are born annually worldwide and 95% occur in developing countries. Low birth weight is a major public health problem of Bangladesh. So an attempt was made to study the incidence of low birth weight (4 parity) showed more low birth weight babies. Women from low socioeconomic condition produced significantly larger number of low birth weight babies as well as short stature. Low maternal height, less educated, illiterate, manual worker mother delivered more low birth weight babies. Preterm birth comprises larger number of low birth weight (LBW 35%). Low height of new born babies also associated with low birth weight. Female babies were higher than the male babies. Preterm babies were lighter (LBW) than the full term babies.Conclusion: The study finds out the incidence of low birth babies, the figure close to the developing countries. The study revealed that maternal age, gestational age, parity, socioeconomic status, maternal weight and disease condition have strong relations with birth weight of babies. Occupation and antenatal check up also affects birth weight of babies.J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 16-22